Doctor Who. The blood of Azrael - Gray, Scott (W. Scott) (Panini Publishing Ltd., 2014)
"A deadly encounter on the streets of 1930s Baghdad-- A terrifying amusement park in the far future -- The eternal psychic prison known as the Hellscape -- A digital world where living beings can be bought or sold -- And a confrontation with the darkest figure in galactic history: the sinister Azrael-- The Doctor is about to mae the worst mistake of his life-- and it will cost him everything he holds dear. Plus an in-depth commentary section" -- page [4] of cover.